Highly Stable Lithium−Sulfur Batteries Promised by Siloxene: An Effective Cathode Material to Regulate the Adsorption and Conversion of Polysulfides. (7th February 2020) - Wang, Yang; Zhou, Liping; Huang, Jingyun; Wang, Xinyang; Xu, Xinling; Lu, Jianguo; Tian, Yang; Ye, Zhizhen; Tang, Haichao; Lee, Shuit‐Tong; Lu, Yingying
Abstract: Designing an appropriate cathode is still a challenge for lithium–sulfur batteries (LSBs) to overcome the polysulfides shuttling and sluggish redox reactions. Herein, 2D siloxene nanosheets are developed by a rational wet‐chemistry exfoliation approach, from which S@siloxene@graphene (Si/G) hybrids are constructed as cathodes in Li‐S cells. The siloxene possesses corrugated 2D Si backbone with abundant O grafted in Si6 rings and hydroxyl‐functionalized surface, which can effectively intercept polysulfides via synergistic effects of chemical trapping capability and kinetically enhanced polysulfides conversion. Theoretical analysis further reveals that siloxene can significantly elevate the adsorption energies and lower energy barrier for Li + diffusion. The LSBs assembled with 2D Si/G hybrid cathodes exhibit greatly enhanced rate performance (919, 759, and 646 mAh g −1 at 4 C with sulfur loading of 1, 2.9, and 4.2 mg cm −2, respectively) and superb durability (demonstrated by 1000 cycles with an initial capacity of 951 mAh g −1 and negligible 0.032% decay rate at 1 C with sulfur loading of 4.2 mg cm −2 ). It is expected that the study presented here may open up a new vision toward developing high‐performance LSBs with siloxene for practical applications. Abstract : Corrugated 2D siloxene nanosheets effectively suppress polysulfides shuttling through the synergistic effects of chemisorption, accelerating polysulfides conversion kinetics, lowering electrochemical polarization, and promoting Li + diffusion. Owing to these merits, such siloxene nanosheets employed in lithium−sulfur battery (LSB) cathodes enable high‐loading LSBs to achieve superior performance, including excellent rate performance and long‐term cyclability.